Memória coletiva e patrimônio histórico: dimensões da legislação municipal em Jundiaí - SP - Camoleze, Jean Marcel Caum [UNESP] (2017)
This dissertation presents a case study concerning the municipal legislation for the preservation of collective memory in the city of Jundiaí - São Paulo, perceiving the sociocultural dynamics existing in the formation of the social identity of the city and the relation of the public power and the civil society with the safeguard and diffusion of memory and historical and cultural heritage. This paper studies the importance of the integration of collective and institutional memory in the formation of individuals and society, in which they are inserted. For that, several theoretical references were used in order to understand memory, its epistemology and its importance in social and citizen formation. Through a sequence of operations that analyzed the historiography of the city of Jundiaí, mainly in the XX and XXI century, referring to laws that seek to safeguard memory and historical preservation, the research analyzes memory as one of the fundamental factors in political, Ideological and social composition of the city. In addition to taking into account that memory is selective and has a dynamic action in the experiences and experiences of individuals, this research will also show the gaps in the preservation of the collective memory of the city of Jundiaí and with that the consequences in the recognition of diverse social groups that (re)construct daily the history of the city and are important sources of information on cultural transformations.